Investigation of Development Opportunities in the Upper Danube Region - Pelt, Ilona; Ritter, Krisztián (Studia Mundi – Economica, 2025)
The Upper Danube Nature Reserve is located in Vojvodina, bordering Hungary’s Duna-Dráva National Park and Croatia’s Kopački Rit Nature Park. Three West Bačka settlements—Bezdan, Monostorszeg, and Kupusina—are integral parts of the Upper Danube Nature Reserve. However, the micro-region formed by these three settlements does not belong to a single municipality. According to Serbian law, the Upper Danube Protected Area falls under the management of the Vojvodina Forests Public Enterprise. However, the villages are under the jurisdiction of Apatin Municipality and the City of Sombor, which complicates the unified development of the affected area. In the first part of our work, we focus on reviewing the literature, paying special attention to the foundations and importance of regional development, and briefly defining rural development. Due to the nature of the topic, we also touch on the theory of local economic development. The second and larger part of the article focuses on the process of our own research, specifically on analyzing primary research results (surveys, structured interviews). Based on our findings, we emphasize the significance of civil organizations in local development, as they are the driving forces of social life. Our survey revealed that residents believe it is important to establish a regional center where all information would be accessible. One of the main recommendations was to make better use of the online space.